Influence of cash flows from the Common Agricultural Policy on liquidity of Slovak trading companies in agriculture in the period 2000-2009 - Zuzana Gallová; Peter Serenčéš (Polityki Europejskie, Finanse i Marketing)
Slovak agriculture is constantly dynamically changing. Accession process to the EU of this sector is important for Slovak agriculture harmonization of agricultural policy related to the Common Agricultural Policy. Integration into the European Union and as well as using the funds of the Common Agricultural Policy significantly affect financial ratios and others indicators as liquidity, solvency and cash flow, which was evaluated the financial statements of assessed financial management. Financial situation of entity is a mirror through which the enterprise is perceived by its surroundings. The situation of liquidity is a determinant, which influences the opinion of external subjects about entity and its financial health. The paper compared the period before and after accession to the European Union (EU), it means the period from 2000 to 2009 with the aim to find the answer if the financial liquidity of Slovak enterprises in agriculture have had a positive or negative development trend.